IMAGE RIGHTS IN THE DIGITAL CONTEXT AND THE LEGAL IMPLICATIONS OF UNAUTHORIZED PUBLICATION OF IMAGES ON SOCIAL MEDIA PLATAFORMS. (REMUNOM, 2025)
This article analyzes image rights in the digital context, especially in light of the unauthorized publication of photographs and videos on social media platforms. The relevance of this research stems from the intensified use of social media and the consequent increase in violations of human dignity, privacy, and honor. The research problem that guides the study consists of investigating the legal implications of the unauthorized publication of images on social networks and the extent to which the Brazilian legal system ensures their protection. The objective is to understand the constitutional and civil foundations of image rights, examine national case law, and discuss the legal limits and exceptions for the use of images without consent. Methodologically, the research adopts a bibliographic and documentary approach, with analysis of constitutional and infra-constitutional provisions, in addition to paradigmatic judicial decisions. It is concluded that the misuse of images gives rise to civil liability, even if no material damage is proven, with moral damage being presumed (in re ipsa), as consolidated by Precedent 403 of the Superior Court of Justice. Furthermore, it should be noted that, although there are exceptional cases of legitimate use of images, human dignity remains an essential parameter in weighing the right to information against personality rights.